Penerapan model problem based learning untuk meningkatkan karakter peduli sosial dan gotong royong pada mata pelajaran pendidikan pancasila sekolah dasar - Nurul Wibowo; Chumdari Chumdari (Universitas Sebelas Maret, 2025)
This study aims to improve the character of social care and mutual cooperation of students through the application of the Problem-Based Learning (PBL) model in Pancasila Education subjects for grade V students of SD Negeri Dukuh 02 in the academic year 2024/2025. This study uses a qualitative approach with the Classroom Action Research (CAR) method which is implemented in two cycles. The research subjects were 17 students. Data were collected through observation, interviews, questionnaires, and documentation. The data analysis technique used Miles and Huberman's interactive data analysis technique with the steps of data reduction, data presentation, drawing conclusions, and verification. The Problem-Based Learning Model was implemented through several stages, namely orienting students to the problem, organizing students to learn, guiding individual and group investigations, developing and presenting discussion results, and analyzing and evaluating problems. The results showed that the implementation of the Problem-Based Learning model steps was effective in improving students' social care and mutual cooperation character. The social care character increased from 71.38% in Cycle I to 82.90% in Cycle II, while the mutual cooperation character increased from 74.04% to 81.88%.